1987
DOI: 10.1161/01.res.61.4.498
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous occurrence of spontaneous localized calcium release from the sarcoplasmic reticulum generates action potentials in rat cardiac ventricular myocytes at normal resting membrane potential.

Abstract: Under certain conditions, spontaneous release of Ca2+ from the sarcoplasmic reticulum occurs in resting mammalian myocardium. In single rat ventricular myocytes, such spontaneous Ca2+ release appears localized rather than homogeneous. When the increase in cytosolic Ca2+ is present in a single locus within a cell, it causes a small depolarization, which, at the normal resting potential, is subthreshold for generating an action potential. However, when spontaneous Ca2+ release occurs simultaneously at more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 17 publications
2
79
0
Order By: Relevance
“…The NCX inward current that is ignited by multifocal spontaneous Ca 2+ release is often sufficient to depolarize the surface membrane to the level required to activate Na + channels (41), and to generate a spontaneous AP (Fig. 4A).…”
Section: +mentioning
confidence: 99%
“…The NCX inward current that is ignited by multifocal spontaneous Ca 2+ release is often sufficient to depolarize the surface membrane to the level required to activate Na + channels (41), and to generate a spontaneous AP (Fig. 4A).…”
Section: +mentioning
confidence: 99%
“…36 -38 Thus, spontaneous Ca 2+ oscillations are not due to transmembrane potential changes but, given the correct initiating conditions, cause traveling Ca 2+ waves, depolarizations, and nondriven action potentials. 4 , 8 , 37 , 39 Although several investigators have identified the nature of the sarcolemmal currents that may underlie these depolarizations, 40 to date no specific antiarrhythmic agents directed toward these underlying currents (e.g., I ti ) have been developed. Thus, we propose that, at least for Purkinje cells from infarcted heart, agents directed toward eliminating aberrant spontaneous Ca 2+ release, which leads to micro Ca 2+ transients, cell-wide waves, and action potentials, may be effective antiarrhythmic agents.…”
Section: Implications Of Findingsmentioning
confidence: 99%
“…In single cardiac myocytes, the synchronous occurrence of spontaneous localized Ca2' release from the sarcoplasmic reticulum can generate "abnormal automaticity" even at a normal resting membrane potential. 46 The argument has been made that endocardial preparations from 1-day-old infarction in dogs demonstrate triggered activity arising from DADs at 360 C, whereas abnormal automaticity may become operative when the temperature is increased to 390 C.6 The ionic mechanism responsible for such a dramatic shift in the arrhythmogenic mechanism is not clear. In the present study, raising the temperature of the tissue bath from 370 to 390 C accelerated the rate of sustained rhythmic activity.…”
Section: Discussionmentioning
confidence: 99%